Forgotten small squares of the old church of San Juan de Dios of Lima - Amorós, Samuel (2023)
The viceregal cities used to have a number of small public spaces attached to churches, which broke the monotony of a generally regular pattern. The two small squares next to the old Juandedian temple in Lima made up a very unusual case in the city and, as time passed, they were the scene for violent historical events that marked Peruvian political life. When it disappeared together with the entire religious edifice, all the memories of its presence were erased, making it necessary to divulge its history for the present and future of society.